Pengaruh Pemberian ZPT Alami dan ZPT Buatan Terhadap Keberhasilan Stek Pucuk Jeruk Lemon (Citrus lemon L.) - Andi Endang Fitria; Siti Khairani; Juhardi Sembiring (UNIVERSITAS LABUHANBATU, 2023)
Lemon lime is one of the horticultural plants that have higher bioactive compounds than lime. Lemon is very much in demand by the public because it contains vitamins, minerals and fiber, besides that it is also often used as a flavor enhancer in regional specialties, so it has a fairly high economic value. The demand is so much that it is difficult for farmers to meet market demand, this is because the lemon cultivation system is so difficult.One way to propagate lemon lime plants can be done by shoot cuttings, namely in this way lemons are easier to root and have lower levels of phenolic compounds which act as factors that support root initiation on cuttings This research aims to find out there is an influence of natural ZPT (coconut water) on the success of Lemon shoot cuttings, To find out there is an effect of giving artificial ZPT (BAP) to the success of Lemon shoot cuttings, To find out there is an interaction of natural ZPT (coconut water) and artificial ZPT (BAP) on the success of Lemon shoot cuttings. This research was conducted Jl. Quarantine Ujung Kec. Medan struggle Kel. Sidorame Barat I Medan. This study consisted of a Complete RandomIzed Block Design (RAK) consisting of 2 factors, namely: Natural ZPT Factor (A) namely: A0 (Control), A1 (150 mg / L), A2 (200 mg / L) and A3 (250 mg / L). While the artificial ZPT factor (B) is: B0 (Control), B1 (0.1 ml / polybag), B2 (0.3 ml / polybag) and B3 (0.5 ml / polybg) there are 16 combinations of treatment and 3 repeats. The results of this study showed that there was an effect of natural ZPT administration on observation of stem diameter, but had no noticeable effect on observation, plant height, number of leaves, length of buds and number of buds. There is no effect of artificial ZPT giving on all observation parameters. There is no interaction on the combination of natural ZPT and artificial ZPT against all observation parameters. Keywords: Lemon, Shoot Cuttings, Natural ZPT, Artificial ZPT.